A novel friction stir diffusion bonding process using convex-vortex pin tools. (1st July 2020) - Ji, S.D.; Wen, Q.; Li, Z.W.
Abstract: In this work, a novel friction stir diffusion bonding (FSDB) method was proposed to eliminate hook when joining thin sheets. Three tools, with several convex-vortex pins were innovatively designed to improve the diffusion bonding effect of the lap interface. Results showed that sound joints, excellently bonded at the lap interface and without hook, were obtained. The lap interfaces on the joints welded using the T-tool and F-tool almost remained intact, thereby indicating that they were formed by diffusion bonding. The material flow behavior was also simulated by FLUENT software and the results showed that the material flow along thickness was significantly enhanced by increasing the pin number. The joint welded by the T-tool showed shear fracture mode. Sound bonding was formed at the lap interface when using the F-tool and thus the joint showed tensile fracture.